Synthetic Optimization of Ellipticine and Antitumor Activity of Novel Hexacyclic Derivatives of Ellipticine - Lin, Jingjing; Tang, Mei; Zhao, Ru; Du, Qianqian; Shen, Longying; Du, Guohua; Zhang, Yafen; Li, Yan; Pan, Xiandao (Current Pharmaceutical Design, 2019)
Background: For decades, a great deal of research work has been done to synthesize ellipticine and its derivatives because of their potential antitumor properties and anti-HIV activities. However, the resonance structures in different media, a low level of solubility at physiological pH and systemic toxicity have prevented the use of ellipticine as a therapeutic agent. Besides, the low yield and complex steps of ellipticine synthesis limit its application. Methods: A high-yield synthetic procedure of ellipticine has been optimized, and the total yield was up to 50% without silica gel column chromatography. Novel hexacyclic ellipticine derivatives were synthesized by coupling ellipticine with o-aminobenzoic acid. Their cytotoxicities against HCT116, MGC803, HT29 and MCF-7 tumor cells were evaluated. Results: The synthesis process of ellipticine was optimized, and the total yield of the synthetic route was increased to 50% through several operation steps optimization. Fourteen ellipticine hexacyclic derivatives were synthesized. The synthetic compounds were screened for anti-tumor activity in vivo and in vitro, and some of the derivatives had good anti-tumor activity. Conclusion: Compared with ellipticine, the compound 1l showed higher antitumor activity and better tolerance to tumor models. The compound 1l treatment increased the percentage of late apoptotic cells from 3.1% (DMSO) to 21.6% (20.0 μM) in NCI-H460 cells. It also was observed the effect of 1l on G2 phase arrest was similar as that of ellipticine. The mechanism of action indicated compound 1l could be a topoisomerase IIα poison. These studies provided the basis for the pharmacodynamics and toxicology of ellipticine, and further clarifies the structureactivity relationship of antitumor activity of ellipticine.
Keywords: hexacyclic derivatives